Teachers’ Perception on Bilingualism and Bilingual Education - Krisma Nurmaya; Nida Husna (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines teachers’ perceptions of bilingualism and bilingual education in Indonesia, focusing on their conceptual understanding as well as perceived challenges and opportunities for implementation. Employing a qualitative descriptive design, data were collected through questionnaires from 16 teachers and in-depth interviews with five teachers across elementary, secondary, and inclusive education settings. The findings indicate that while teachers generally acknowledge the cognitive and social benefits of bilingualism, several barriers impede effective bilingual education. Notably, 68.8% of teachers identified inadequate training as a major challenge, and 62.6% pointed to limited instructional resources and curriculum misalignment. Despite these obstacles, teachers recognized substantial opportunities to strengthen bilingual education, including enhanced professional development, greater community involvement, and increased use of technology to support language learning. These insights underscore the need for targeted policy support and capacity-building initiatives to improve the quality and sustainability of bilingual education in Indonesia.